The Implementation of Right-Fulfillment to the Education of Elementary School Students in the COVID-19 Pandemic Situation - Harisman Harisman; M. Syukran Yamin Lubis; Muhammad Rifqi Syukran Lubis (Randwick International of Social Science Journal, 2021)
This study is intended to explain the legal protection given to elementary school children to get the right to education during the COVID 19 period. Because education for children is a child's right that must be fulfilled as a human right. Moreover, the right to education has been explicitly guaranteed in the Amendment to the 1945 Constitution. For this reason, legal research is carried out with an empirical juridical approach which intends to study and analyze the workings of law in society by using secondary data and primary data. The secondary and primary data collected were analyzed qualitatively, then the results were described. Based on an analysis conducted on research conducted in Firdaus Village, Serdang Bedagai Regency, that the right to education for elementary school children during the COVID 19 period was still being fulfilled despite the prohibition on conducting face-to-face learning processes at schools. The implementation of education is carried out through distance learning meetings in the network and distance learning outside the network. In addition, it was also found that there was limited face-to-face learning. However, the use of this learning method takes into account the development of the COVID-19 situation and also the facilities owned by schools, teachers and the condition of students in participating in learning. Schools and teachers evaluate children's education to determine the learning process that will be used.